Systemic Bank Restructuring and Macroeconomic Policy. (International Monetary Fund, 1997)
Edited by William Alexander, Jeffrey M. Davis, Liam P. Ebrill, and Carl-Johan Lindgren, this volume discusses cross-country restructuring experiences building on the foundation laid by its predecessor Band Soundness and Macroeconomic Policy. It discusses broad principles and actions to guide policy makers in restructuring their banking systems.